2018
DOI: 10.1038/s41386-018-0177-7
|View full text |Cite|
|
Sign up to set email alerts
|

JHU-083 selectively blocks glutaminase activity in brain CD11b+ cells and prevents depression-associated behaviors induced by chronic social defeat stress

Abstract: There are a number of clinically effective treatments for stress-associated psychiatric diseases, including major depressive disorder (MDD). Nonetheless, many patients exhibit resistance to first-line interventions calling for novel interventions based on pathological mechanisms. Accumulating evidence implicates altered glutamate signaling in MDD pathophysiology, suggesting that modulation of glutamate signaling cascades may offer novel therapeutic potential. Here we report that JHU-083, our recently developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 100 publications
(159 reference statements)
0
38
0
Order By: Relevance
“…However, given that inhibitors of GTK are not commercially available to combine with pharmacological GLS1 inhibition, an attempt to use glutamine antagonism was explored as proof‐of‐concept for improving therapeutic efficacy by blocking global metabolic pathways from glutamine utilization. Thus, we employed our previously reported global glutamine antagonist, termed JHU083 (ethyl 2‐(2‐amino‐4‐methylpentanamido)‐DON), a prodrug of 6‐diazo‐5‐oxo‐ l ‐norleucine (DON) . We generated patient‐derived pancreatic orthotopic tumors (JHU094), the same tumors used in our initial in vivo metabolomics analysis above, which were found to closely mimic the molecular, pathobiological, and clinical characteristics of PDAC .…”
mentioning
confidence: 99%
“…However, given that inhibitors of GTK are not commercially available to combine with pharmacological GLS1 inhibition, an attempt to use glutamine antagonism was explored as proof‐of‐concept for improving therapeutic efficacy by blocking global metabolic pathways from glutamine utilization. Thus, we employed our previously reported global glutamine antagonist, termed JHU083 (ethyl 2‐(2‐amino‐4‐methylpentanamido)‐DON), a prodrug of 6‐diazo‐5‐oxo‐ l ‐norleucine (DON) . We generated patient‐derived pancreatic orthotopic tumors (JHU094), the same tumors used in our initial in vivo metabolomics analysis above, which were found to closely mimic the molecular, pathobiological, and clinical characteristics of PDAC .…”
mentioning
confidence: 99%
“…in treating CNS disorders are currently under investigation. For instance, JHU-083, a prodrug of a classic GLS1 inhibitor L-DON, inhibits GLS1 activity in microglia to block inflammatory response and prevent depression-associated behaviors induced by chronic social defeat stress (39). Our study provided strong evidence that the inhibition of GLS1 by CB839 also alleviated neuroinflammation in acute brain injury, indicating bright prospects of GLS1 inhibitors in clinical application.…”
Section: Discussionmentioning
confidence: 62%
“…There are emerging links between CNS inflammation and glutamate signaling underlying depression (18). Furthermore, a recent study reported that pharmacological inhibition of microglial glutamate production ameliorates chronic stress-induced depressive-like behaviors (19). Considering that mTOR signaling also regulates the immune and inflammatory systems via modulation of NF-κB and STAT3 signaling pathways (ref.…”
Section: Discussionmentioning
confidence: 99%